2017
DOI: 10.1111/luts.12155
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effects of Formulated Food of Peucedanum japonicum Extract and Saw Palmetto Extract in Male Patients with Lower Urinary Tract Symptoms

Abstract: Food formulated with P. japonicum extract and SPE may be useful to decrease frequency of nighttime urination and residual urine volume in male patients with LUTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Multiple studies have reported that oxidative stress increases in bladder tissues in diabetes (Changolkar et al 2005;Kanika et al 2011;Ha et al 2013;Chen et al 2015;Lin et al 2020;Wang et al 2021;Laddha and Kulkarni 2022). Oxidative stress has also been reported from clinical studies of various types of LUTD other than diabetes (Antunes-Lopes et al 2019;Matsuo et al 2020), and the urinary presence of oxidative stress indicators such as 8-hydroxy-2′doexyguanosine has been proposed as biomarker for LUTS in general (Kageyama et al 2018;Matsumoto et al 2019). Interestingly, treatment for 14 days with the antioxidants resveratrol (10 mg/kg/day, p.o.)…”
Section: Oxidative Stressmentioning
confidence: 98%
“…Multiple studies have reported that oxidative stress increases in bladder tissues in diabetes (Changolkar et al 2005;Kanika et al 2011;Ha et al 2013;Chen et al 2015;Lin et al 2020;Wang et al 2021;Laddha and Kulkarni 2022). Oxidative stress has also been reported from clinical studies of various types of LUTD other than diabetes (Antunes-Lopes et al 2019;Matsuo et al 2020), and the urinary presence of oxidative stress indicators such as 8-hydroxy-2′doexyguanosine has been proposed as biomarker for LUTS in general (Kageyama et al 2018;Matsumoto et al 2019). Interestingly, treatment for 14 days with the antioxidants resveratrol (10 mg/kg/day, p.o.)…”
Section: Oxidative Stressmentioning
confidence: 98%
“…47 SPE + Selenium + Lycopene in combination with tamsulosin is more efficacious than single therapies in improving IPSS and increasing maximal urinary flow-rate in patients affected by LUTS/BPH. Other combination therapies, such as with tamsulosin, [48][49][50] Urtica dioica, 39 Pinus pinaster 36 and Peucedanum japonicum, 51 have also shown positive results in co-prescriptions for treating BPH and BPH-linked disorders.…”
Section: Clinical Application Of Spe In Urinary System Diseasesmentioning
confidence: 99%
“…[ 139 ] 3. [ 74 ] Potentilla chinensis Rosaceae Chinese Cinquefoil Aerial part (aqueous extract) 1. Attenuated RA-induced DO in rats 2.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, clinical effects of the extract were investigated in male patients with LUTS. It improved urodynamic parameters and subjective symptom scores without reported adverse drug reactions [ 74 ]. These investigations suggest its possible therapeutic application in OAB treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation